2013
DOI: 10.2478/s11536-013-0170-9
|View full text |Cite
|
Sign up to set email alerts
|

An education-behavioural intervention improves adherence to statins

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…Most (20/32) of the included studies were conducted in North America [ 21 24 , 26 30 , 32 , 36 , 37 , 43 , 45 51 ], with 9 conducted in Europe [ 20 , 31 , 34 , 35 , 38 , 39 , 41 , 42 , 44 ] and 3 in Asia [ 25 , 33 , 40 ]. The median sample size for the intervention group was 202 (range: 15–29,042) and the median study duration was 12.0 months (range: 3 months–2 years).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most (20/32) of the included studies were conducted in North America [ 21 24 , 26 30 , 32 , 36 , 37 , 43 , 45 51 ], with 9 conducted in Europe [ 20 , 31 , 34 , 35 , 38 , 39 , 41 , 42 , 44 ] and 3 in Asia [ 25 , 33 , 40 ]. The median sample size for the intervention group was 202 (range: 15–29,042) and the median study duration was 12.0 months (range: 3 months–2 years).…”
Section: Resultsmentioning
confidence: 99%
“…Of those that did, half indicated that statins were prescribed for secondary CVD prevention [ 20 22 , 25 , 33 , 44 46 , 48 ]. Other indications included primary hypercholesterolemia [ 35 ], diabetes [ 28 , 32 ] and elevated CVD risk [ 36 , 37 , 39 , 51 ]. Five studies selected patients based on poor adherence to statin therapy [ 24 , 26 , 31 , 36 , 38 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the intervention was codesigned by community pharmacists and primary care doctors with the goal of establishing a standard intervention that would be able to be implemented in both of these health professional fields. In the case of interventions where reminders were used, there are studies where adherence improves after intervention in the community pharmacy and in the hospital setting . On the other hand, when the intervention is about providing education on the importance of adherence to treatment and other issues related to the disease, there are studies that do not find improvement at the end of the study in community pharmacy nor in the hospital environment .…”
Section: Discussionmentioning
confidence: 99%
“…In the case of interventions where reminders were used, there are studies where adherence improves after intervention in the community pharmacy 19,42 and in the hospital setting. 45,46 On the other hand, when the intervention is about providing education on the importance of adherence to treatment and other issues related to the disease, there are studies that do not find improvement at the end of the study in community pharmacy 21 nor in the hospital environment. 22,26 Data suggest that in order to obtain the improvement in adherence, identifying the cause of nonadherence and choosing the most appropriate intervention for the patient's situation should be part of the intervention.…”
Section: Discussionmentioning
confidence: 99%